REPRESENTASI SUREALISME PADA VIDEO KLIP LAGU MAN UPON THE HILL KARYA STARS AND RABBIT - Nur Dwimas Setiawan; Sri Wahyuningsih (Universitas Prof. Dr. Moestopo (Beragama), 2021)
The music video for Man Upon The Hill by Stars and Rabbit can steal attention because it is able to present unique and interesting visuals. The purpose of this study was to determine the representation of the meaning of surrealism in the video clip Man Upon The Hill by Stars and rabbit. This research uses descriptive qualitative research methods. Data collection using the method of observation, in-depth interviews, and documentation. Informants were selected using purposive sampling technique. The technique of checking the validity of the research data used the source triangulation technique. The result of this research is the relationship between humans and nature, representations of several scenes: First, symbols such as the pentagram have the meaning of a dimension of life. Second, the Third Eye Chakra is the highest consciousness. Third, the arrangement of roots to form a gate represents a gate to a different dimension. Fourth, the tree root guitar represents how nature communicates, the melody that sounds from nature. Fifth, the arrangement of floating stones in a circle is the cycle of life. Sixth, black skin is a representation of the balance of the life cycle. Seventh, women with horses represent warriors, children represent purity.